2008
DOI: 10.1111/j.1600-6143.2007.02097.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Allograft Survival and Modulation of T-Cell Alloreactivity Induced by Inhibition of MMP/ADAM Enzymatic Activity

Abstract: Recent studies have shown significantly increased expression of matrix metalloproteinases (MMP) and disintegrin-type metalloproteinases (ADAM) during allograft rejection. In this regard, our previous studies have demonstrated contrasting roles for MMP-2 and MMP-9 during allograft rejection: MMP-2-deficiency enhanced allograft survival while MMP-9-deficiency decreased allograft survival. The aim of this study was to determine the effect of broad-spectrum MMP/ADAM inhibition on the pathogenesis of allograft reje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…MMP-2 null mice have decreased T cell alloreactivity and inflammatory cytokine release, while MMP-9 null mice have increased alloreactivity and cytokine release (14). Broad-spectrum inhibition of MMPs leads to decreased inflammatory cell chemotaxis and improves cardiac graft survival (26). However, these results may be tissue specific, as MMP-9 null mice have improvement in survival of tracheal allografts (30).…”
Section: Mechanisms Of Mmp Action In Kidney Diseasementioning
confidence: 99%
“…MMP-2 null mice have decreased T cell alloreactivity and inflammatory cytokine release, while MMP-9 null mice have increased alloreactivity and cytokine release (14). Broad-spectrum inhibition of MMPs leads to decreased inflammatory cell chemotaxis and improves cardiac graft survival (26). However, these results may be tissue specific, as MMP-9 null mice have improvement in survival of tracheal allografts (30).…”
Section: Mechanisms Of Mmp Action In Kidney Diseasementioning
confidence: 99%
“…Inhibition of other in vitro T cell activation responses by tetracyclines have also been demonstrated, such as chemotaxis, up-regulation of CD40 ligand, and cytokine production, most notably that of IFN [61][62][63][64]. In most assays, significant inhibitory effects are observed at clinically achievable drug concentrations (5-15 μM).…”
Section: Leukocytesmentioning
confidence: 99%
“…In vitro experiments have shown B cell proliferation and chemotaxis to be inhibited by doxycycline, in some studies at concentrations as low a 1 μg/ml [64,67]. In addition, in vitro immunoglobulin (Ig) production is decreased by as much as 86% by minocycline or doxycycline (5-10 μg/ml), Ig class switching is inhibited, and expression of B cell differentiation genes is reduced [67,68].…”
Section: Leukocytesmentioning
confidence: 99%
“…Use of a broad spectrum MMP inhibitor significantly reduced T-cell infiltration and improved survival of the cardiac allograft, whereas MMP-9 gene-inactivated mice had significantly increased cellular infiltration and impaired cardiac allograft survival. 4 Whether TIMP-1 deficiency or overexpression also alters cardiac allograft function and survival warrants further investigation.…”
Section: To the Editormentioning
confidence: 99%
“…Use of a broad spectrum MMP inhibitor significantly reduced T-cell infiltration and improved survival of the cardiac allograft, whereas MMP-9 gene-inactivated mice had significantly increased cellular infiltration and impaired cardiac allograft survival. 4 Whether TIMP-1 deficiency or overexpression also alters cardiac allograft function and survival warrants further investigation.What about the role of MMP-9 in other cardiac diseases? Independent studies clearly showed that deficiency of MMP-9 but also of MMP-2 significantly reduced inflammation and improved cardiac function after myocardial infarction or hypertension (reviewed in Vanhoutte et al 5 ).…”
mentioning
confidence: 99%